The role of holm oak edges in the control of disturbance and conservation of plant diversity in fire-prone landscapes (Forest Ecology and Management, 2013)
Holm oak (Quercus rotundifolia) woodlands have been able to persist in ﬁre-prone landscapes in northern Portugal where they seem to play a relevant role in community and landscape level patterns and processes, namely in the control of disturbance events and in the maintenance of biodiversity. In this research we tested the following hypotheses: (i) holm oak woodlands affect ﬁre behavior, mainly by disrupting and delaying ﬁre spread; (ii) disruption and delaying of ﬁre spread is due to ﬁre extinction at the edge of woodlands; and (iii) plant diversity is favored by frequent low-intensity ﬁres as a result of the control of ﬁre spread by holm oak woodland edges. We sampled herbaceous, shrub and tree structure and herbaceous plant composition across edges of holm oak woodlands with known recent contact with ﬁre. Using BehavePlus we converted structural data into fuel models and simulated ﬁre behavior for the locations sampled along the exterior–interior gradient of the woodlands. Our results indicate that holm oak woodlands play a relevant role in the control of ﬁre spread and in the maintenance of plant diversity. We found differences in simulated maximum rate of ﬁre spread (ROS) and ﬁreline intensity (FLI) between outside and inside woodlands as well as a 100% probability of ﬁre extinction when fuel moisture was >12% and wind speed at 10 m aboveground was <40 km h1 , supporting the self-extinction hypothesis. We found also that richness and abundance of herbaceous plants varied between the interior and exterior of the woodland, with higher values outside the woodland, and that plant composition along the interior– exterior gradient had distinct patterns. These variables and the pattern of plant distribution were also signiﬁcantly affected by time since last ﬁre event. We conclude that holm oak woodlands affect ﬁre behavior by interrupting ﬁre spread at the edge zone and that ﬁre-created edges affect herbaceous plant species richness, abundance and distribution by maintaining habitat diversity, which increased plant diversity at patch and landscape levels. Based on our results and other evidence, we developed a conceptual model of the dynamics of ﬁre, landscape structure, and plant diversity in ﬁre-prone landscapes where holm oak patches persist.